Analysis of Capital Structure Decisions of Issuers Before and After Initial Public Offering on the Indonesia Stock Exchange - Dewa Putu Yohanes Agata L. Sandopart (Varied Knowledge Journal, 2025)
This study analyzes the changes in capital structure decisions of issuers before and after Initial Public Offering (IPO) on the Indonesia Stock Exchange during the 2018-2022 period. Employing a quantitative approach with a longitudinal retrospective design, this study involved 74 non-financial companies, generating 444 firm-year observations. The results revealed three main findings. First, there was a significant decrease in all capital structure proxies post-IPO, with the Debt to Equity Ratio declining from 1.874 to 1.562 (p<0.05). Second, the speed of capital structure adjustment reached 0.487, higher than the pre-IPO period (0.312). Third, companies conducting IPOs in hot market conditions experienced a more drastic leverage reduction (Δ=-0.778; p<0.05) compared to cold market conditions (Δ=-0.089; p>0.05). Panel data regression analysis confirmed that firm size and asset tangibility positively influenced leverage, while profitability, growth, business risk, and IPO market conditions exerted negative effects. This study integrates trade-off theory, pecking order theory, and market timing theory in explaining capital structure phenomena during the IPO transition period. The primary contribution of this research lies in providing empirical evidence from emerging markets and developing a partial adjustment model that impacts the dynamics of post-IPO capital structure adjustment.